Social interaction-mediated lifespan extension of Drosophila Cu/Zn superoxide dismutase mutants - Ruan, Hongyu (National Academy of Sciences, 2008)
Beneficial effects of social interaction on aging have been studied in humans and other species. We found that short-lived Drosophila mutants of the antioxidant enzyme Cu/Zn superoxide dismutase displayed a robust lifespan extension, with improved stress resistance and motor ability, upon cohousing with active flies of longer lifespan or younger age. Genetic, surgical, and environmental manipulations revealed motor and sensory components in behavioral interactions required for the lifespan extension induced by cohousing. Our results provide a definitive case of beneficial social interaction on lifespan and a useful entry point for analyzing the underlying molecular networks and physiological mechanisms.